Non-Linear Load Characterisation Using Orthogonal Apparent Power Decompositions - Dimitrijevic, Marko A.; Stevanovic, Dejan; Litovski, Vanco B. (Elektronika ir Elektrotechnika, 2021)
There is no generally accepted definition for apparent power components in circuits with non-sinusoidal conditions. The decomposition of apparent power has been the subject of many discussions and is still an open topic. Over the years, a number of apparent power decompositions have been proposed and analysed, usually in the context of compensation. These analyses were performed by means of simulations or by calculating quantities using measurements on a simple test circuit. Here, we present a unique system capable of simultaneous apparent power decompositions for non-sinusoidal conditions in real-time. The system can calculate power components related to various power decompositions. The system’s capabilities are demonstrated on non-linear load characterization.